DESIDOC moves into new building - DESIDOC, Director (DESIDOC Journal of Library & Information Technology, 2002)
DESIDOC-a self-accounting and Independent establishment of DRDO since July 1970 - Was partially housed in the monumental building known as Metcalfe House. Uptil now, some technical and administrative divisions of DESIDOC were located in different hutments spread all over the sprawling Metcalfe House campus. The new building of DESIDOC is located in the campus and has three wings. B-Wing, a Single storeyed block, was occupied in April 1986 by the Printing Division and is equipped with phototypesetter and photo-offset machines.